(untitled) (Pakistan Journal of Society, Education and Language (PJSEL), 2020)
This study was conducted in Chakdara, District Dir Lower, which is one of the major cities of District Dir Lower and where there is a huge camp for Afghan refugees. The objectives of this study are to find out the impacts of Afghan refugees on the security situation of Chakdara. Apart from the local population of Chakdara, which is 29,712, some 11,184 refugees live in camp while some of the refugees live out of camp in Chakdara and surrounding areas. In order to know whether these refugees have any impact on the security situation of the area, a sample size of 379 respondents was selected through stratified random sampling from the local community using Sekaran method (2003). Data was collected through interview schedule and their views about the impacts of refugees on security were found. The study proved that the massive influx of Afghan refugees to Chakdara has not only created social, political, economic, environmental and ecological problems, but also caused an alarming threat to Pakistan’s internal security. Because of the presence of refugees, drastic changes came in the social setup of local community. Local people have adopted new trends of dressings, cooking, art, music etc. Besides, the crime rate such as theft, drug trafficking, street crimes, and beggary has been increased enormously in Chakdara. They also have a role in increased number of beggars in the area. It is clear from the study that the Afghan refugees have aggravated the local social system. The study also shows that the Afghan refugees are the main source of disputes in the area.